Novel Electroactive Therapeutic Platforms for Cardiac Arrhythmia Management - Juwei Yang; Longfei Li; Yiran Hu; Zhou Li; Wei Hua (Advanced Science, 2025)
Abstract Electroactive platforms have gained significant attention for their ability to convert various types of energy into electrical signals, offering promising applications in diverse biomedical fields. In cardiovascular care, these platforms are increasingly valued for their innovative solutions in managing cardiac functions and disorders. By regulating electrical activity in the heart, electroactive platforms offer novel methods for managing abnormal heart rhythms. This review explores the latest advancements in electroactive systems, categorizing them based on their energy sources and mechanisms, such as self‐powered and conductive systems. It also highlights their applications in arrhythmia management, including monitoring, intervention, pacing, and repairing. Finally, the challenges, limitations, and future opportunities for clinical translation of these technologies are discussed.